2017
DOI: 10.1142/s0217590815501155
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Regression Approach to Fdi in Vietnam: Province-Level Evidence

Abstract: Foreign direct investment flows into Vietnam have increased significantly in recent years and are distributed unequally between provinces. This article aims to investigate the locational determinants of foreign direct investment in 62 Vietnamese provinces and whether spatial dependence is a significant factor that both researchers and policy-makers should take into account. We report that province-specific per-capita income, secondary education enrolment, labor costs, openness to trade, and domestic investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Also, some papers apply Blonigen et al's approach to investigate spatial linkages at sub‐national (e.g., regional) level, such as Ledyaeva (2009), Sharma, Wang, and Sunny Wong (2014), Hoang and Goujon (2014, 2019), Esiyok and Ugur (2017), and Gutiérrez‐Portilla, Maza, and Villaverde (2019b). There is a clear reason justifying a regional approach: the fact that this type of linkages is stronger the higher the level of data disaggregation, namely the smaller the unit of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some papers apply Blonigen et al's approach to investigate spatial linkages at sub‐national (e.g., regional) level, such as Ledyaeva (2009), Sharma, Wang, and Sunny Wong (2014), Hoang and Goujon (2014, 2019), Esiyok and Ugur (2017), and Gutiérrez‐Portilla, Maza, and Villaverde (2019b). There is a clear reason justifying a regional approach: the fact that this type of linkages is stronger the higher the level of data disaggregation, namely the smaller the unit of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the dynamics of FDI at the subnational level can help us precisely identify the location behaviour of MNEs and the peculiarities of regions within a country that attract FDI (McCann & Mudambi 2005). Recent studies narrowed the research scope to a precise scale and suggested that apart from the traditional location determinants, the presence of third‐region effects significantly influence FDI location decisions within a country (Casi & Resmini 2014; Esiyok & Ugur 2017; Fonseca & Llamosas‐Rosas 2019; Gutiérrez‐Portilla et al . 2019b).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nonetheless, there are some studies on similar topics: for example, Bezborodova (2011) and . However, many of the existing studies by international authors are devoted to spatial analysis of FDI in: the Russian Federation (Kuznetsova, 2015;Kuznetsov, 2016), the EU (Ascani et al, 2016), Spain (Gutiérrez-Portilla et al, 2019), Romania (Goschin, 2017), Vietnam (Esiyok, Ugur, 2017), China (Xingqiang, Lixia, 2008), etc.…”
Section: Literature Reviewmentioning
confidence: 99%